2020
DOI: 10.1007/s40037-020-00579-z
|View full text |Cite
|
Sign up to set email alerts
|

Getting to know our non-traditional and rejected medical school applicants

Abstract: None

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…Such variables could be of relevance given the complementarity of the social, cultural, symbolic, and economic capitals to the student's capital in determining both the intent to join medical school but inevitably the achievement of goal posts while navigating medical graduation. 37,38 A study of such parameters would help in designing a 360-degree plan of action that begins before entry into the medical program, moulds to the progression level needs, and in later years, provides seamless support to transit to graduate medical education and the health professions workspace.…”
Section: Discussionmentioning
confidence: 99%
“…Such variables could be of relevance given the complementarity of the social, cultural, symbolic, and economic capitals to the student's capital in determining both the intent to join medical school but inevitably the achievement of goal posts while navigating medical graduation. 37,38 A study of such parameters would help in designing a 360-degree plan of action that begins before entry into the medical program, moulds to the progression level needs, and in later years, provides seamless support to transit to graduate medical education and the health professions workspace.…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands, there are also strong indications that HPE students are unrepresentative for the population as a whole, and concerns exist that the change from lottery admission to selection has negatively influenced student diversity and equal opportunities in admissions. 21 For example, a retrospective cohort study showed that male applicants, applicants with a Turkish, Moroccan, Surinamese or Dutch Caribbean migration background, applicants without parents whose wealth belongs to the top-10% of the population, and applicants without healthcare professional parents, have significantly lower odds of being selected. 32 In spite of men making up 50% of the student population that is eligible to apply for HPE, they make up only about 30% of the HPE applicant pool and admitted student population.…”
Section: Introductionmentioning
confidence: 99%
“… 32 However, international research on the detailed demographics of potentially eligible student and applicant pools of HPE programmes, and how exactly the factors which influence self-selection play a role, is scarce. 21 Wouters et al 15 provided an account of factors that influence Dutch potential applicants’ motivation to apply for medicine. However, it is not sufficiently known to what extent this process differs between traditional and non-traditional students, nor how people in their networks influence their decision-making.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 This lack of diversity also occurs in other nursing and healthcare programs in the Netherlands due to the lack of role models and the pressure of the family. 3,4 Bos interviewed Bachelor of Nursing minority students about the barriers other students potentially experience in choosing a healthcare program. 4 The students said that the family had a large influence on the students' academic life, not supporting them to select a nursing, dental, or healthcare program, because other programs were perceived as more valuable to achieving "success" in life.…”
Section: Introductionmentioning
confidence: 99%